Western enterprises on eastern markets: The German perspective - Klaus-Dieter Schmidt; Petra Naujoks (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1993)
The paper offers a vision of the future of cross-border activities between Germany and the Central and East European reform countries. It provides a comprehensive theoretical framework and it presents some stylized facts. It focuses on three prominent areas: trade in goods and services, off-shore processing and foreign direct investment. Although trade in goods and services is still the dominant form of cross-border activities, other forms make up mightily. Industry and country variables strongly influence the type of activities. Trade and off-shore processing are predominantly derived from comparative advantages (especially cheap labour) in Heckscher- Ohlin industries. Foreign direct investment, however, can be found mainly in (mobile) Schumpcter industries.
Keywords: 330; Außenwirtschaft; Lohnfertigung; Direktinvestition; Deutschland; Osteuropa